Jeitinho as a Coping Strategy Used by Brazilian International Students for Acculturative Stress - Alves Nishioka, Silvia; Akol, Defne (Journal of International Students, 2019)
This mixed-method study examined whether Brazilian students in the US use an indigenous problem-solving practice, jeitinho, as a coping strategy for acculturative stress. Forty-two participants answered an online survey, which was a culmination of demographic information, the Acculturative Stress Scale for International Students, BriefCOPE, jeitinho questionnaire, and three open-ended questions about how Americans may perceive jeitinho. Results showed that a negative dimension of jeitinho was associated with nonadaptive coping strategies, but it was not a significant predictor of acculturative stress. Qualitative themes highlighted the multidimensionality of jeitinho, which could help in students’ adjustment (positive) or reinforce stereotypes and prejudices (negative) against Brazilians. Findings elucidate the complexity of jeitinho Brazilian students can be mindful about and when to use it to avoid stereotyping.